2011
DOI: 10.1080/09537287.2011.564218
|View full text |Cite
|
Sign up to set email alerts
|

Shop floor characteristics influencing the use of advanced planning and scheduling systems

Abstract: The purpose of this article is to investigate how the manufacturing process, the shop type and the data quality, i.e. the shop floor characteristics, influence the use of advanced planning and scheduling (APS) systems in production activity and control (PAC). The methodology implemented is a multiple case study at three case companies. Each company has different shop floor characteristics, but all use a scheduling module in an APS system, which supports production scheduling. A theoretical framework is develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…While IT and automated transfer between planning systems may be important for formal routine information, social network governance and face-to-face communication may be more important for informal and spontaneous information. In addition, the feedback of shared information is important for information quality (Jäckel et al , 2006; Ivert, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While IT and automated transfer between planning systems may be important for formal routine information, social network governance and face-to-face communication may be more important for informal and spontaneous information. In addition, the feedback of shared information is important for information quality (Jäckel et al , 2006; Ivert, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…APS systems are computational decision tools used to support process planning and scheduling that use optimization models to create detailed plans inside the manufacturing environments. Ivert (2012a) observed that the primary ability of APS systems is that of finding an optimal assignment of resources to sequences of operations, considering critical elements such as process flow, resource availability, floor shop capacities, precedence constraints, and load balance. In addition, Hvolby and Steger-Jensen (2010) considered that APS systems might take into account other types of constraints, including the availability of raw materials, inventory levels, costs, sales, and demands.…”
Section: Scheduling Ecosystemmentioning
confidence: 99%
“…By doing that, they prevent some of the shop floor uncertainties that ERP systems are bound to encounter on the shop floor. APS is recently standardized and presented as an advanced scheduling technology and how this technology can handle uncertainties is still an open research topic [12].…”
Section: Dealing With Unscheduled Events In a Typical It Configurationmentioning
confidence: 99%
“…In stable and reliable environments, these analytical tools and computerized systems can yield expected performance results, especially for the high level material and capacity planning decisions [3]. However, shop types with high uncertainty and complexity where many factors affect the decision making process can be substantially challenging [8][9][10][11][12]. As such, very few of the advanced models and systems that address dynamic scheduling/ re-scheduling decisions have influenced and provided guidelines in the industrial practice [2,13,14].…”
Section: Introductionmentioning
confidence: 99%